IMPLEMENTASI KEBIJAKAN PENYALURAN HIBAH DAN BANTUAN SOSIAL DI BADAN KESATUAN BANGSA DAN POLITIK KOTA BONTANG - Natalia Trisnawati (Jurnal Paradigma (JP), 2017)
This study aimed to describe the implementation of Bontang City goverment social grant distribution in the Board of National Unity and Politics of Bontang. This research uses descriptive qualitative research methods, and the data collected through interviews and documentation. Results of the research shows that the implementation of social grant distribution in the Board of National Unity and Politics of Bontang is not optimal in sense of the implementation of the beneficiary  is still lacking.